Effect of pH on visible-light-driven Bi2WO6nanostructured catalyst synthesized by hydrothermal method - Anukorn Phuruangrat (2018)
© 2014 Elsevier Ltd. All rights reserved. In this research, effect of pH on phase, morphologies and photocatalytic activities of Bi2WO6synthesized in the precursor solution with the pH of 2-12 by the 180 °C and 20 h hydrothermal reaction is reported. The as-synthesized Bi2WO6products were characterized by X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectrophotometry, Brunauer-Emmett-Teller (BET) isotherm, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and UV-visible spectroscopy. The photocatalytic activities of the as-synthesized Bi2WO6products were evaluated via the photodegradation of rhodamine B (RhB) under visible-light radiation. The results showed that the precursor solution pH had an important influence on the photocatalytic activities of the Bi2WO6nanocatalyst. When the precursor solution pH was 2, the RhB degradation exhibited the highest decolorization efficiency of 98% within 100 min.